Dyssynergic Defecation: A Comprehensive Review on Diagnosis and Management - Sadeghi, Anahita; Akbarpour, Elham; Majidirad, Fatemeh; Bor, Serhat; Forootan, Mojgan; Hadian, Mohammad-Reza; Adibi, Peyman (Turkish Journal of Gastroenterology, 2023)
About one-third of chronically constipated patients have an evacuation disorder, and dyssynergic defecation is a common cause of the evacuation disorder. In dyssynergic defecation, the coordination between abdominal and pelvic floor muscles during defecation is disrupted and patients cannot produce a normal bowel movement. The etiology of dyssynergic defecation is still unknown. Although a detailed history taking and a careful examination including digital rectal examination could be useful, other modalities such as anorectal manometry and balloon expulsion test are necessary for the diagnosis. Biofeedback therapy is one of the most effective and safe treatments. Here, we provide an overview of dyssynergic defecation as well as how to diagnose and manage this condition. Cite this article as: Sadeghi A, Akbarpour E, Majidirad F, et al. Dyssynergic defecation: A comprehensive review on diagnosis and management. Turk J Gastroenterol. 2023;34(3):182-195.